Biodiversity of microbial consortia isolated from traditional fresh sheep cheese Karakačanski skakutanac - Viviana Corich; Alessio Giacomini; Dafni-Maria Kagkli; Maura D'Andrea; Tomislav Pogačić; Enrico Baldan; Andreja Čanžek Majhenič; Tanja Obermajer; Irena Rogelj; Dubravka Samaržija (Mljekarstvo)
The aim of this study was to assess the structure of indigenous microbial community associated with traditional fresh sheep cheese Karakačanski skakutanac and to preserve autochthonousmicrobial consortia. Eleven cheeses were sampled during production season (April-September) and subjected to microbiological analysis. Bacterial DNA was isolated by Maxwell®16 DNA system from99 microbial consortia harvested from three culture media (M17, Rogosa, CATC) on the 1st, 2nd and 3rd day of the cheese shelf life. The extracted bulk DNA (n = 99) was used as a template forPCR-ARDRA and PCR-DGGE analysis. There were no dramatic shifts in the bacterial number and structure of the microbial consortia harvested on the 1st, 2nd or 3rd day of the cheese shelf life neitherduring period of sampling. Lactococcus lactis subsp. lactis reached the number of 107-108 CFU g-1, while Leuconostoc pseudomesenteroides, Enterococcus faecalis, and Lactobacillus versmoldensis were identified only at lower dilutions (10-2 - 10-3). This first polyphasic microbiological-molecular study of the Karakačanski skakutanac indicated the main LAB representatives associated with the cheese. Obtained autochthonous microbial consortia present a valuable pool of strains for further genetic and functional characterizations.